The Human SLC7A5 (LAT1): The Intriguing Histidine/Large Neutral Amino Acid Transporter and Its Relevance to Human Health - Scalise, Mariafrancesca; Galluccio, Michele; Console, Lara; Pochini, Lorena; Indiveri, Cesare (Frontiers in Chemistry, 2018)
SLC7A5, known as LAT1, belongs to the APC superfamily and forms a heterodimeric amino acid transporter interacting with the glycoprotein CD98 (SLC3A2) through a conserved disulfide. The complex is responsible for uptake of essential amino acids in crucial body districts such as placenta and blood brain barrier. LAT1/CD98 heterodimer has been studied over the years to unravel the transport mechanism and the role of each subunit. Studies conducted in intact cells demonstrated that LAT1/CD98 mediates a Na+ and pH independent antiport of amino acids. Some novel insights into the function of LAT1 derived from studies conducted in proteoliposomes reconstituted with the recombinant human LAT1. Using this experimental tool, it has been demonstrated that the preferred substrate is histidine and that CD98 is not required for transport being, plausibly, involved in routing LAT1 to the plasma membrane. Since a 3D structure of LAT1 is not available, homology models have been built on the basis of the AdiC transporter from E.coli. Crucial residues for substrate recognition and gating have been identified using a combined approach of bioinformatics and site-directed mutagenesis coupled to functional assays. Over the years, the interest around LAT1 increased because this transporter is involved in important human diseases such as neurological disorders and cancer. Therefore, LAT1 became an important pharmacological target together with other nutrient membrane transporters. Moving from knowledge on structure/function relationships, two cysteine residues, lying on the substrate binding site, have been exploited for designing thiol reacting covalent inhibitors. Some lead compounds have been characterized whose efficacy has been tested in a cancer cell line.